The coastal ichthyofauna of the Mediterranean coral reef: the case of Mljet National Park (Croatia, southern Adriatic Sea) - Lovrenc Lipej; Danijel Ivajnšič; Danijel Ivajnšič; Valentina Pitacco; Borut Mavrič; Domen Trkov; Petar Kružić (Frontiers in Marine Science, 2024)
The authors studied the structure of the coastal fish assemblage in a temperate coral reef within a marine protected area in order to provide a baseline information on the occurrence and temporal distribution of fish and to highlight the importance of the coral reef to ichthyofauna. The coastal fish assemblage was investigated at two sites in Veliko jezero (Mljet National Park) in the southern Adriatic Sea with a non-destructive SCUBA visual technique in the period from 2013 to 2021. Altogether, 38 fish taxa were recorded on the right bank (coral reef) and 36 species on the left bank. The presence of the coral reef at a depth range between 9 m to 12 m is the main factor differentiating the fish fauna in these two areas, which are otherwise governed by the same environmental factors. At the coral reef a decrease in fish diversity was discovered with a steady regression from 2013 to 2021.